CHARACTERISTICS OF CLARIFICATION PROCESS IN NITRIFICATION – DENITRIFICATION SYSTEM FOR WASTE WATER WITH N-NH3 - Ari Setiawan; Bayu Hari Nugroho (Diponegoro University, 2020)
Research on combinations of activated sludge processes - The clarifier is an attempt to improve the performance of the activated sludge process. In this system, the clearing works as a sediment deposition. The treatment process is expected to operate at a high biomass concentration and produce a compact system for optimal deposition speed. Some of the things covered in this research are, to calculate the rate of sludge deposition in the purifier and to measure the level of water purity or turbidity of the activated sludge treatment process. In this research, synthetic wastewater is used. The ventilation tank is made of plexiglass, with a total volume of 150 Liter. The clarifier is made of plexiglass with an inverted prism shape. The results show that the deposition rate and the degree of purity of water are influenced by the concentration of bacteria Mixed Liquor Suspended Solid (MLSS) or bacteria. The results show that the concentration of MLSS or bacteria increased, the deposition rate decreased. This can be seen in the MLSS 130 ppm which shows faster deposition rate than the MLSS 355 ppm. In the case of turbidity, larger MLSS results, increased turbidity, indicate an accurate flux.